An analysis on the effects of multi-currency system to the economy of Zimbabwe: a case of Marange 2009-2014 - Sigauke, Sinziya (Midlands State University, 2015)
There are a number of reasons that led to the collapse of the Zimbabwean economy for almost a decade prior to February 2009. Zimbabwe experienced the dramatic rise of hyperinflationary which led millions of Zimbabweans abandoning the country to find greener pastures somewhere across the globe. In response to the chaotic hyperinflationary period that had defined the country’s economic environment, Zimbabwe adopted the Multi-Currency System (MCS) in January 2009. The purpose of this paper is to analyze the effects of multi- currency system to the economy of Zimbabwe particularly to the rural populace in Marange. Data was collected from 29% purposively selected respondents through interviews and unstructured questionnaires. Using descriptive statistics to analyze the primary data the research found that although the MCS has generally improved positively the quality of life for some people, the majority still remain in poverty considering the quality of life indicators like the national datum line especially on rural populace. Hence, this study is therefore important as it will shed some insight and provide recommendations to the macro-economic problems being faced by the Marange post dollarization economy. Thus the government must adopt a single currency to avoid exchange rate problems as well as reduce shortages of smaller denominations. This study was purely qualitative in nature and data soliciting techniques that includes questionnaire and semi-structured interviews targeting the households, school heads, shop owners, health providers so as to acquire detailed information about the performance of these crucial sectors; education, health and food.